Sedimentation in a humid, interior, extensional basin: The Cenozoic Li Basin, northern Thailand - Gary Nichols (2018)
Facies distributions extensional basins are controlled by a combination of factors including local and regional tectonics, climate, hinterland characteristics and base-level changes. During the mid-Cenozoic, northern Thailand was a region in which active basin formation was occurring as a result of regional extension related to major strike-slip faults. It was also a time when the climate was relatively humid. The Li Basin is one of about 40 Cenozoic basins in northern Thailand that have a fill of continental facies, and it is also one of a number of basins that contain economic coal deposits. Analysis of the geographical and temporal distribution of facies in the Li Basin indicates that it had internal drainage fed by rivers that supplied water and sediment to extensive floodplain and lake environments. Variations in the sediment supply were an important control on the relative development of fluvial channel and muddy overbank facies during periods of high clastic input and peat swamp and lacustrine facies when elastic input was lower. Changes in palaeosol type and the occurrence of peat deposits indicate that there was a trend towards drier conditions through the period of deposition of the available sections (Late Oligocene to Miocene). The Li Basin succession provides an example of a small (500 km2) extensional basin formed in a humid climate with interior drainage and periods of low elastic sediment supply. These conditions resulted in an association of facies deposited in permanent lakes, peat swamps, wet and dry floodplains, fluvial channels and local alluvial fans. The relationships between depositional facies and tectonic, climatic and sediment supply controls established in this case study may be applicable to other rift and transtensional basins.